2021
DOI: 10.1371/journal.pone.0252327
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the molecular basis of the dominant negative effect of myosin XI tails on P-bodies

Abstract: The directional movement and positioning of organelles and macromolecules is essential for regulating and maintaining cellular functions in eukaryotic cells. In plants, these processes are actin-based and driven by class XI myosins, which transport various cargos in a directed manner. As the analysis of myosin function is challenging due to high levels of redundancy, dominant negative acting truncated myosins have frequently been used to study intracellular transport processes. A comparison of the dominant neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This system was then successfully applied to interfere with the localization and polarity of phosphorylated myosin in apical contraction during the morphogenesis of the Ciona siphon. Our results demonstrated that the MLCP-BcLOV4 system is a powerful tool for the study of biomechanical mechanisms during organ morphogenesis compared with chemical inhibitor [ 21 , 22 , 23 ] and dominant negative mutation approaches [ 24 , 56 ], which have high inhibition efficiency on the activity of myosin but still have limitations on the working range and time. The MLCP-BcLOV4 system could rapidly change the localization and polarity of myosin II at the subcellular level, which greatly improved the accuracy and reduced the potential side effects of the experimental manipulation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This system was then successfully applied to interfere with the localization and polarity of phosphorylated myosin in apical contraction during the morphogenesis of the Ciona siphon. Our results demonstrated that the MLCP-BcLOV4 system is a powerful tool for the study of biomechanical mechanisms during organ morphogenesis compared with chemical inhibitor [ 21 , 22 , 23 ] and dominant negative mutation approaches [ 24 , 56 ], which have high inhibition efficiency on the activity of myosin but still have limitations on the working range and time. The MLCP-BcLOV4 system could rapidly change the localization and polarity of myosin II at the subcellular level, which greatly improved the accuracy and reduced the potential side effects of the experimental manipulation.…”
Section: Discussionmentioning
confidence: 94%
“…At present, some low-molecular-weight compounds are widely used to inhibit the activity of NM II, such as blebbistatin [ 21 ], ROCK inhibitor Y-27632 [ 22 ], MLCK inhibitor ML-7 [ 23 ], etc. The function of actomyosin can also be blocked by myosin light chain dominant negative mutation [ 24 ]. However, disadvantages of these methods limit their applied range.…”
Section: Introductionmentioning
confidence: 99%
“…Here, our data support a model whereby TYMaV IBs are tethered to myosin motors through direct binding of P to the GTD domain of myosin XI. This anchoring mechanism, to our knowledge, has not been previously reported for other plant viral proteins but parallels the movement model of membraneless P‐bodies in which DCP1 interacts with the myosin GTD domain (Steffens et al ., 2014; Stephan et al ., 2021). Hijacking a motor protein also accounts for the intracellular movement of CaMV P6 IBs.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the Ror1 tail domain exerts a dominantnegative effect and phenocopies a ror1 mutant Expression of the C-terminal tail domain of myosins is known to cause a dominant-negative effect on the function of different myosin classes in various experimental systems, including plants (Avisar et al, 2009;Bittins et al, 2009;Burns et al, 1995;Stephan et al, 2021). We, therefore, wondered whether (over)expression of the Ror1 tail domain would also lead to a dominant-negative effect.…”
Section: Ror1 Partially Colocalizes With Peroxisomesmentioning
confidence: 99%